Realization of single-photon emitters with high brightness and high stability and excellent monochromaticity - Chen, Shengyao (2024)
Two-dimensional (2D) semiconductor single-photon emitters (SPEs) have great potential in various light quantum technologies owing to their perfect collection efficiency. However, various 2D semiconductor SPEs are difficult to simultaneously fulfill a combination of high brightness, high stability, and excellent monochromaticity, owing to challenges in single-frequency emitting, single-frequency intensity, and emitting stability. Here, we present a feasible strategy that, based on a controllable wrinkling technique, realizes simultaneous high brightness, high stability, and excellent monochromaticity in a monolayer WSe2 nano-bulge SPE array with a designable and controllable local uniform large-strain gradient. The SPEs exhibit exceptional performance in SPE generation probability up to about 70% and possess high single-frequency brightness and excellent emitting stability. Our innovative method represents a powerful approach to generating SPEs in 2D materials through strain engineering.